Le système solaire - Encrenaz, Thérèse, 1946- (Savoirs actuels. Astrophysique., 2003)
This work propounds a synthetic view of the properties of all the components of the solar system. Its comments stress the importance of the physics and chemistry processes that determined its formation and evolution. It is a new version of "The Solar System" that had been the main reference work published in 1987. It has been brought up to date with additional information.